Enhancing the Students’ Speaking Skill Using Three Step Interview and Numbered Heads Together - Ratnawati, Sri Rahayu; Yuliasri, Issy; Hartono, Rudi (Universitas Negeri Semarang, 2018)
This research aimed to investigate the effectiveness of Three Step Interview (TSI) and Numbered HeadsTogether Techniques (NHT) to enhance speaking skill for the students having different motivation levels and to show if there is any interaction between teaching techniques and motivation. The participants of the research were the students of survival English Class Level of Nissan Fortuna English Course, Kudus. The research method of this study was quantitative by using 2x2 factorial experimental research designs. The data collection was done by giving questionnaire and conducting pre-test and post-test and was analyzed by using ANOVA. This study found that (1) TSI and NHT are effective to enhance speaking skill of students with different motivation level, (2) Enhancing speaking skill of the high motivated students using TSI is more effective than using NHT, (3) Enhancing speaking skill using TSI to the low motivated students is more effective than using NHT, (4) There is no interaction between the techniques and students‘ motivation. This study concluded that TSI and NHT can be used as techniques to enhance the students‘ speaking skill no matter how students‘ motivational level is.